Small Scale Drug Trafficking and Territorial Control in Latin America - Saborío, Sebastián (FLACSO - Sede Ecuador, 2019)
This article analyses the phenomena of territorial control that is carried on by small scale drug trafficking groups in Latin American cities. It shows that existing publications on this topic take for granted what “territorial control” is, but end up referring to different social processes. Leaning in the concepts of territory, territoriality and territorialization, the author defines which elements shape the different modalities of territorial control implemented by small scale drug trafficking groups. In this way, he provides an analytical tool composed by different indicators: who are the subjects controlled by drug gangs, what is the extension, modality and objectives of territorial control and how do these groups influence political and associative life as well as other spheres of everyday life of the communities in which they are located.